2011
DOI: 10.1177/0021998311429877
|View full text |Cite
|
Sign up to set email alerts
|

Experimental fabrication and characterization of out-of-plane fiber waviness in continuous fiber-reinforced composites

Abstract: This study presents the development of fabrication techniques and experimental measurements of out-of-plane fiber waviness in a continuous fiber-reinforced polymer composite. Literature on characterization and fabrication techniques was briefly reviewed. Three fabrication methods were developed: the transverse-strip method, ply-drop method, and constant-thickness ply-drop method. Experimental characterization demonstrated that specimens with a range of waviness parameters can be easily manufactured. The most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 22 publications
0
56
0
Order By: Relevance
“…Many wind turbine blades are made using vacuum resin infusion. This manufacturing method makes IP waves more likely to occur (Wang, 2012).…”
Section: Common Blade Flaw Typesmentioning
confidence: 99%
“…Many wind turbine blades are made using vacuum resin infusion. This manufacturing method makes IP waves more likely to occur (Wang, 2012).…”
Section: Common Blade Flaw Typesmentioning
confidence: 99%
“…al. developed three methods of fabricating out-of-plane waviness which were used to quantify a wider class of wrinkles by introducing additional parameters [19]. However, those wrinkles are 2 also constructed from cosine functions fitted to empirical misalignment measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, except for some work on the phenomena involved during the appearance of defects like "yarn waviness", "buckles" and "weave pattern heterogeneity", there are few studies treating of the mesoscopic defects [10,[14][15][16]. Concerning the effect of the mesoscopic defects, except some studies on the effect of the fibre waviness on the UD composite [17][18][19], there are few studies to our knowledge on this aspect [21]. However, it has been shown that they are more recurring during complex preforms shaping [6,10].…”
Section: Introductionmentioning
confidence: 99%